Alkaloid Accumulation and Distribution within the Capsules of Two Opium Poppy (Papaver somniferum L.) Varieties - Péter Májer; Éva Zámboriné Németh (Plants, 2024)
The goal of this study was to clarify the role of capsule size and morphology in the alkaloid yield of poppy. In 2023, two industrial varieties from large-scale cultivation were investigated. Three classes of capsule size (large, medium, and small) and four organelles (wall, placenta, disc, and thalamus) of the seedless capsule were studied for their mass proportions and alkaloid contents. In ‘Meara’, large capsules had 41% lower total alkaloid levels than smaller ones. In ‘Morgana’, there was no difference in total alkaloids between size groups, but large capsules had higher contents of codeine and thebaine. Among the four organelles, the wall represented the largest mass in both varieties (60–67%), while the disc and the thalamus gave the lowest proportions (below 9%). In the variety ’Meara’, the highest alkaloid contents appeared in the wall (2.69% d.w.), followed by the placenta, and the other two parts. ‘Morgana’ accumulated the highest alkaloid content (3.72% d.w.) in the placenta. Morphine follows the trend of the total content, while codeine and thebaine may differ. Accurate information on the accumulation of alkaloids in the generative organs may contribute to increasing effectiveness in target-oriented breeding and optimization of cultivation with an appropriate choice of variety.